Maternal and perinatal death surveillance and response: a systematic review of qualitative studies - Willcox, ML; Okello, IA; Maidwell-Smith, A; Tura, AK; van den Akker, T; Knight, M (World Health Organization, 2022)
Objective To understand the experiences and perceptions of people implementing maternal and/or perinatal death surveillance and response in low- and middle-income countries, and the mechanisms by which this process can achieve its intended outcomes.